Self-Expandable Metal Stent Placement for Closure of a Leak after Total Gastrectomy for Gastric Cancer: Report on Three Cases and Review of the Literature - Raimondo, Dario (Hindawi Publishing Corporation, 2014)
In the setting of the curative oncological surgery, the gastric surgery is exposed to complicated upper gastrointestinal leaks, and consequently the management of this problem has become more critically focused than was previously possible. We report here three cases of placement of a partially silicone-coated SEMS (Evolution Controlled Release Esophageal Stent System, Cook Medical, Winston-Salem, NC, USA) in patients who underwent total gastrectomy with Roux-en-Y end-to-side esophagojejunostomy for a gastric adenocarcinoma. The promising results of our report, despite the small number of patients, suggest that early stenting (through a partially silicone-coated SEMS) is a feasible alternative to surgical treatment in this subset of patients. In fact, in the treatment of leakage after total gastrectomy, plastic stents and totally covered metallic stents may not adhere sufficiently to the esophagojejunal walls and, as a result, migrate beyond the anastomosis. However, prospective studies with a larger number of patients might assess the real effectiveness and safety of this procedure.